1956
DOI: 10.1021/ja01588a062
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium Isotope Effects on the Air Oxidation of Cumene

Abstract: Communications to the Editor Vol. 7S with the recorded melting point of 220°for 6-chloro-3(2H )benzofurunone semicarbazone.7Proof of Structure of IV by Conversion to 2-Chloro-4methoxybenzoic Acid.-Two grams (0.01 mole) of IV was dissolved in 50 ml. of water containing 2 g. of XaOH and heated to the refluxing temperature. Methyl sulfate (2.ñ g., 0.02 mole) was added slowly and the refluxing continued for 2 hours. At the end of this time, a solution of 8 g. of KMiiO( in 100 ml. of water was added slowly and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1957
1957
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…7). These isotope effects are in fair agreement n-it11 the values obtained by Boozer et al (14) from the oxidation of curnene and CGI-IjC (CD3) 2H, i.e., rateII/rate, = 0.88. This deuteriuru (10) and Vzclrzitinskzz (12) For personal use only.…”
Section: Uni?zhibited Oxidation Of A-methylstyrenesupporting
confidence: 89%
“…7). These isotope effects are in fair agreement n-it11 the values obtained by Boozer et al (14) from the oxidation of curnene and CGI-IjC (CD3) 2H, i.e., rateII/rate, = 0.88. This deuteriuru (10) and Vzclrzitinskzz (12) For personal use only.…”
Section: Uni?zhibited Oxidation Of A-methylstyrenesupporting
confidence: 89%
“…Russell (14) calculated the true primary isotope effect for hydrogen abstraction, (kpcc)/(lcpc9,D, to be 5.5 at 60" using cumene-a-d containing 58.4% deuterium. Boozer et al (15) compared cumene with two samples of P-deutero-cumene containing 1.4 and 3.0 atoms of deuterium per molecule.The secondary isotope effect for propagation was measured by addingp-nitrophenol or 2,4-dichlorophenol to inhibit the normal termination process. Values of (kPCC)/(kpC9, ,,-, in the range 1.05-1.27 were obtained at 65".…”
Section: Resultsmentioning
confidence: 99%
“…Russell, 17 Walling 16 and Boozer et al 31 have reported the formation of α-methylstyrene in the autoxidation of cumene and have suggested that it arises from cumylperoxyl radicals. Although no mechanisms were proposed, a plausible route is shown in Scheme 4.…”
Section: Oxidation Of Cumene and Tert-butylbenzenementioning
confidence: 99%